Dissecting mitosis by RNAi in Drosophila tissue culture cells - Maiato, H (2003)
interference (RNAi) in cultured cells of Drosophila melanogaster. This procedure is particularly useful for the analysis of genes for which genetic mutations are not available or for the dissection of complicated phenotypes derived from the analysis of such mutants. With the advent of whole genome sequencing it is expected that RNAi-based screenings will be one method of choice for the identification and study of novel genes involved in particular cellular processes. In this paper we focused particularly on the procedures for the proper phenotypic analysis of cells after RNAi-mediated depletion of proteins required for mitosis, the process by which the genetic information is segregated equally between daughter cells. We use RNAi of the microtubule-associated protein MAST/Orbit as an example for the usefulness of the technique.